2010
DOI: 10.2478/v10011-010-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin, Nitrite and Paraoxonase/Arylesterase Concentrations in Cement Plant Workers

Abstract: Kratak sadr`aj: Izlaganje cementnoj pra{ini na radnom mestu povezano je s pove}anim rizikom od promena na jetri, plu}nih bolesti i nastanka kancera. Mogu}i mehanizmi koji uzrokuju bolesti su smanjeni antioksidativni kapacitet i po vi{e na lipidna peroksidacija u plazmi. U skladu s tim, u ovoj studiji prou~avani su nivoi paraoksonaze (PON1) -arilesteraze (AE), grelina, HDL-C, LDL-C i nitrita (NOx) u serumu kod radnika izlo`enih cementnoj pra{ini. U studiji je u~e stvovalo dvadeset osam radnika u cementari i 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…For instance, human exposure to cement dust has been shown to induce several respiratory, mutagenic and gastrointestinal disorders [11][12][13]. According to Aydin et al [14], Al-Neaimi et al [15] and Alvear-Galindo et al [16], occupational exposure to cement dust is associated with an increased risk of liver abnormalities, pulmonary disorders and carcinogenesis. Similarly, cases of chest pain, cough and eye problems were prevalent among village residents that were exposed to cement dust [17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, human exposure to cement dust has been shown to induce several respiratory, mutagenic and gastrointestinal disorders [11][12][13]. According to Aydin et al [14], Al-Neaimi et al [15] and Alvear-Galindo et al [16], occupational exposure to cement dust is associated with an increased risk of liver abnormalities, pulmonary disorders and carcinogenesis. Similarly, cases of chest pain, cough and eye problems were prevalent among village residents that were exposed to cement dust [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cement dust also irritate the skin, mucous membrane of the eyes and the respiratory system in general. The deposition of cement dust in the respiratory tract leads to increased pH values which irritate the exposed mucous membranes and impair respiration (Mwaiselage et al, 2005, Fell et al, 2003, Aydin et al, 2010and Zeleke et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Further research is needed to throw more light on the complex relationships between serum ghrelin and HDL levels and the enhanced lipid peroxidation in patients with parasitic infections. [33] Final remarks Overall, our results showed that the serum ghrelin concentration was significantly decreased in patients infected with G. lamblia as compared to the healthy group (Figure 1), whereas the serum melatonin (Figure 2), serum glucose ( Figure 3) and serum cholesterol (Figure 4) levels were significantly increased in giardiasis patients as compared to the healthy group. However, it should be noted that our research included a relatively small number of male patients only.…”
Section: Serum Cholesterol Levels In Giardiasis Patients and Healthy mentioning
confidence: 69%